Peran Motivasi, Komitmen Organisasi Dan Lingkungan Kerja Terhadap Kinerja Karyawan Balai Pengawas Obat Dan Makanan - Nurussaumi; Zainur Hidayah; Etty Puji Lestari (Coopetition : Jurnal Ilmiah Manajemen, 2020)
The challenges faced by the National Food and Drug Agency in Bengkulu in carrying out the task are large, both internally and externally, in the effort to achieve organizational performance. The demand for bureaucratic reform in the government system in Indonesia requires organizations to make changes in many aspects. The purpose of this study was to analyze whether motivation, organizational commitment and work environment affect performance. This research was conducted on employees of the National Food and Drug Agency in Bengkulu with a population of 63 people. The sample used was 61 people. The independent variables in this study are motivation, organizational commitment and work environment, while the dependent variable is performance. Variable measurements are carried out using a likert scale. Data analysis using multiple linear regression analysis using SPSS 16 software. The results of the analysis showed that motivation, organizational commitment and work environment simultaneously or together had a significant and positive effect on performance by 49.3% while 50.7% were influenced by other variables. outside of this research model. While partially there is no influence between motivation variables on performance, there is a significant and positive influence of organizational commitment and work environment on the performance of the employees of the National Food and Drug Agency in Bengkulu.